FACTORS THAT AFFECT THE INCOME OF SMALL TRADERS IN THE AREA OF THE TOMB OF THE HERO AND STUDION MAULANA YUSUF SERANG CITY - Ahmad Mukhlis (Yayasan Education and Social Center, 2021)
The main problem faced by most small traders in Serang is a problem that is now a social phenomenon. Many obstacles, not only influenced by factors derived from internal small traders, such as physical conditions that are not possible, limited capital, limitations of education andlack of income obtained, but problems faced by small traders such as the number of competitors, the condition of the crisis that has not ended, or the disaster that has recentlyplagued the country so that in this case affect small traders in developing their business that directly affects the income they receive. Therefore this study aims to find out the dominant factors that affect income. In this study, the authors focused more on the income factors of small traders as one of the factors for the fulfillment of their lives and will examine more deeply about: factors that affect the income of small traders in the Heroes Cemetery and Studion Maulana Yusuf Serang City. Therefore, the method used is quantitative descriptive with special approach techniques, with the collection of data obtained from the dissemination of questionnaires and data. While the data analysis tool uses multiple linear regressions. The results of the study are based on the table of test results Ftable Fcalculated by (2,835) > F table of (2.35). Thus it can be assumed that there is a significant influence of age variables, education level, working hours, work experience, on income variables.